Coronoid process sclerosis as a reproducible and highly heritable risk predictor of medial coronoid disease in labrador retrievers - Deboutte, Birgit; Stock, Emmelie; Kromhout, Kaatje; van der Wal, Annika; Vanderperren, Katrien; Broeckx, Bart J. G. (Frontiers in Veterinary Science, 2026)
IntroductionCanine elbow dysplasia (CED) is an important cause of exclusion during training for assistance dogs, making improved selection strategies essential for these programs. Although selective breeding has been applied for decades, progress in reducing CED prevalence has been limited, partly because many breeding programs rely on radiography rather than the more accurate computed tomography (CT). This study aimed to evaluate CT-based scoring of specific features in breeding dogs, as a tool to reduce the prevalence of medial coronoid disease (MCD)-the most common manifestation of CED-in their offspring.MethodsAn observational study was conducted on a group of Labrador Retrievers from two assistance dog breeding programs where CT is used routinely for screening. Six CT features were scored in parents without primary lesions, and their association with MCD occurrence in offspring was analyzed. Inter-rater agreement was assessed, and for features deemed reproducible, CT reports from a subset of offspring were rescored and narrow-sense heritability was estimated using Bayesian statistical methods.ResultsSclerosis of the coronoid process (CP) was the strongest predictor of offspring MCD risk [odds ratio = 4.6, 95% CI = (1.3; 16.5)], had sufficiently high inter-rater agreement and showed high heritability.DiscussionCP sclerosis proved to be a significant and reproducible phenotype with high heritability, encouraging the use of this feature in CT-based scoring protocols in breeding programs to improve selection strategies and accelerate progress in reducing MCD prevalence.